An Internal Instrument Calibration Simulator for Multi-Channel SAR - Krieger, Gerhard; et al. (IEEE International Geoscience and Remote Sensing Symposium (IGARSS), 2018)
The increased complexity of multi-channel SAR sensors and the real-time on-board phase/amplitude correction requirement poses new challenges for the calibration, which cannot rely on current calibration techniques. On the other hand, the digital hardware utilized in multi-channel SAR systems, offer entirely new opportunities for the calibration such as on-board error correction and digital calibration. An internal calibration strategy for future digital beamforming SAR instruments is detailed and its performance analyzed using a dedicated calibration simulator.
Keywords: calibration; multi-channel calibration; internal SAR calibration; SAR internal errors; instrument calibration simulator